10. Q10f
Save videos to My Cheatsheet for later, for easy studying.
Video Solution
Q1
Q2
Q3
L1
L2
L3
Similar Question 1
<p>Factor each expression.</p><p><code class='latex inline'> \displaystyle x^4 - 625 </code></p>
Similar Question 2
<p>Factor.</p><p><code class='latex inline'>\displaystyle{\frac{y^4}{81}-\frac{x^4}{625}}</code></p>
Similar Question 3
<p>Factor.</p><p><code class='latex inline'>(x-5)^2-9</code></p>
Similar Questions
Learning Path
L1 Quick Intro to Factoring Trinomial with Leading a
L2 Introduction to Factoring ax^2+bx+c
L3 Factoring ax^2+bx+c, ex1
Now You Try
<p>Factor fully</p><p><code class='latex inline'>\displaystyle 64x^6 -25 </code></p>
<p>Expanding confirms that <code class='latex inline'>x^2 - 1 = (x - 1)(x + 1)</code> and also that <code class='latex inline'>x^3 - 1 = (x - 1)(x^2 + x + 1)</code>. Make conjectures and determine similar factorings for </p><p><code class='latex inline'>x^4 - 1</code></p>
<p>Factor the following fully and simplify.</p><p><code class='latex inline'>\displaystyle (x^2 - 3)^4 - 1 </code></p>
<p>Factor.</p><p><code class='latex inline'> \displaystyle x^8 - 1 </code></p>
<p> Factor the following fully using <code class='latex inline'>a^2 - b^2 = (a - b)(a + b)</code> formula.</p><p><code class='latex inline'>\displaystyle y^4 - 81 </code></p>
<p>Factor.</p><p><code class='latex inline'>\displaystyle x^{8}-256 </code></p>
<p> Factor the following using <code class='latex inline'>a^2 - b^2 = (a - b)(a + b)</code> formula.</p><p><code class='latex inline'>\displaystyle 16x^4 - 625y^4 </code></p>
<p>Factor fully.</p><p><code class='latex inline'>\displaystyle x^6 -4y^2 </code></p>
<p>Factor <code class='latex inline'> \displaystyle 18x^5 - 512xy^2 </code></p>
<p>Factor each expression.</p><p><code class='latex inline'> \displaystyle x^4 - 625 </code></p>
<p>Factor the following fully.</p><p><code class='latex inline'>x^4-1=(x^2-1)(x^2+1)</code></p>
<p>Factor.</p><p><code class='latex inline'> \displaystyle 3x^2 - 27(2 -x)^2 </code></p>
<p> Factor the following using <code class='latex inline'>a^2 - b^2 = (a - b)(a + b)</code> formula.</p><p><code class='latex inline'>\displaystyle (x + y)^2 - w^2 </code></p>
<p>Factor.</p><p><code class='latex inline'>\displaystyle{\frac{y^4}{81}-\frac{x^4}{625}}</code></p>
<p>Factor each expression.</p><p><code class='latex inline'>a^4-16</code></p>
<p>Factor.</p><p><code class='latex inline'>a^4 -16</code></p>
<p>Factor.</p><p><code class='latex inline'>(x-5)^2-9</code></p>
<p>Factor each expression.</p><p> <code class='latex inline'>289x^6-81</code></p>
<p>Factor completely</p><p><code class='latex inline'> \displaystyle x^4 -1 </code></p>
<p>Factor.</p><p><code class='latex inline'> \displaystyle 9(y - 1)^2-25 </code></p>
<p>Factor.</p><p><code class='latex inline'>(m - n)^2-(2m + 3n)^2</code></p>
<p> Factor the following fully using <code class='latex inline'>a^2 - b^2 = (a - b)(a + b)</code> formula.</p><p><code class='latex inline'>\displaystyle x^8 - 1 </code></p>
<p>Factor fully.</p><p><code class='latex inline'>144a^4-121</code></p>
<p>Factor each expression.</p><p><code class='latex inline'> \displaystyle x^4-16 </code></p>
<p>Factor.</p><p><code class='latex inline'>1-9a^2b^4</code></p>
How did you do?
I failed
I think I failed
I think I got it
I got it
Another question?
Found an error or missing video? We'll update it within the hour! 👉
Report it
Save videos to My Cheatsheet for later, for easy studying.